(Ba, Sr)3MgSi2O8 structure change caused by Ba/Sr replacement. Issue 1 (15th October 2014) - Yonezaki, Yoshinori
Abstract : Crystal structure of Ba x Sr3– x MgSi2 O8 has been determined by Raman spectroscopy and X-ray diffraction. The solid solution series have glaserite-type layered structures made of corner-sharing SiO4 tetrahedra and MgO6 octahedra. Ba 2+ and Sr 2+ ions are sandwiched in between the layers. Raman spectroscopy has found that structural symmetry changes at x = 0.5 and 2.5. Structural refinement by the Rietveld method has clarified that the symmetry changes occur among C 2 ( Z = 4), P 3 m 1 ( Z = 1), and P 3 ( Z = 3). They originate in SiO4 tilting caused by size mismatch between alkali–earth cations and their site spaces. For x ≤ 0.5, SiO4 tilting occur every other interlayer space, whereas for x ≥ 2.5, all the SiO4 tilt.